PENGENALAN KOSAKATA BAHASA INGGRIS MELALUI MEDIA SPEAKING PYRAMID KELOMPOK B TK AL-MUNASIRIN - Nisrina Maghfira Richandika; Sri Nurlaily; Hapsa Kamaruddin (Universitas Darunnajah, 2023)
Vocabulary is one of the components of language that is very important in communicating or speaking. The stage of introducing English to early childhood begins with the introduction of vocabulary that is used in everyday vocabulary. The problems studied in this study are: 1. How is the process of introducing English vocabulary through the Speaking Pyramid media at Al-Munasirin Kindergarten, 2. Can the introduction of English vocabulary through the Speaking Pyramid media at Al-Munasirin Kindergarten be improved. This research was carried out using the Classroom Action Research method at Al-Munasirin Kindergarten which is located on Jl. Employee I No.22, Karang Tengah, Tangerang City. The results showed: 1. English vocabulary in children can be improved through the Speaking Pyramid media at Al-Munasirin Kindergarten through the stages of the cycle, namely pre-cycle, first cycle, and second cycle. 2. In the pre-cycle the child has not developed because it can be seen from the average result of 38%, in the first cycle the child begins to develop because it is seen from the average result of 66%, and in the second cycle, the child achieves its development because it can be seen from the results an average of 87%. Thus, it can be concluded that this action research is successful and the hypothesis of increasing English vocabulary recognition is acceptable.